Perbandingan Kurikulum Pendidikan Indonesia dan Finlandia - Irdhan Epria Darma Putra; Rusdinal Rusdinal; Azwar Ananda; Nurhizrah Gistituati (Journal on Education, 2023)
This study was conducted to determine the design of the education system adopted from the Finnish education system. Therefore, a comparison of the Indonesian and Finnish education curricula is needed so that it can be considered in making decisions and policies to improve the Indonesian education curriculum. The use of methods in this study is revie literature from several national journal research results to compare educational curricula, especially Indonesia and Finland. The results showed that the Indonesian education curriculum can be categorized as low because it refers to the five aspects of the curriculum, which are curriculum objectives that depend on (1) student readiness and independence; (2) curriculum material that is emphasized to each school by involving students in the announcement of the material studied; (3) learning media based on student comfort in the learning process; (4) learning strategies that can advance student achievement; and (5) a learning process that does not bind students by giving a lot of homework from the teacher. The results of this research contribute to improving the quality of Indonesian education and policy making in the Indonesian education curriculum.